In vivo electroporation of skeletal muscle: threshold, efficacy and relation to electric field distribution - Gehl, Julie; Sørensen, Thyge H.; Nielsen, Kurt; Raskmark, Povl; Nielsen, Steen L.; Skovsgaard, Torben; Mir, Lluis M. (Biochimica et biophysica acta, 1999)
In vivo electroporation is increasingly being used to deliver small molecules as well as DNA to tissues. The aim of this study was to quantitatively investigate in vivo electroporation of skeletal muscle, and to determine the threshold for permeabilization. We designed a quantitative method to study in vivo electroporation, by measuring uptake of 51Cr-EDTA. As electrode configuration influences electric field (E-field) distribution, we developed a method to calculate this. Electroporation of mouse muscle tissue was investigated using either external plate electrodes or internal needle electrodes placed 4 mm apart, and eight pulses of 99 μs duration at a frequency of 1 Hz. The applied voltage to electrode distance ratio was varied from 0 to 2.0 kV/cm. We found that: (1) the threshold for permeabilization of skeletal muscle tissue using short duration pulses was at an applied voltage to electrode distance ratio of 0.53 kV/cm (±0.03 kV/cm), corresponding to an E-field of 0.45 kV/cm; (2) there were two phases in the uptake of 51Cr-EDTA, the first indicating increasing permeabilization and the second indicating beginning irreversible membrane damage; and (3) the calculated E-field distribution was more homogeneous for plate than for needle electrodes, which was reflected in the experimental results.